Pendampingan Penerapan Media Pembelajaran Inovatif Berbasis E-Learning Untuk Peningkatan Kompetensi Pada Guru SMAN 1 Anjir Pasar - Karyadiputra, Erfan; Ibrahim, Ibrahim; Kumala, Sari (Politeknik Negeri Banjarmasin, 2019)
The majority of teachers at Anjir 1 Public High School Market are skilled in using technology devices such as smartphones and computers. Supported by computer laboratory facilities and internet access in schools so that teachers should be able to make maximum use of these facilities in addition to learning support media as well as supporting the improvement of teacher competencies as professional educators. This community service activity aims to provide edmodo social media-based e-learning training that is very practical and easier to use for beginners so that in addition to the teacher having knowledge of e-learning as well as having the skills to support the learning process without limited space and time. The method used was in the form of an introduction to Edmodo's e-learning as well as the creation of an Edmodo account, followed by training in making digital exam questions using the Edmodo quiz facility involving students of Anjir Pasar 1 Public High School. The results of the activity found that the teacher can make digital exam questions with various types of questions such as true false, short answer, fill in the blank, multiple choice and matching. Keywords: edmodo, e-learning, teacher, quiz